The Influence of Working Capital to Total Asset, Debt to Equity Ratio, And Inventory Turnover Ratio towards Profit Growth In Indonesia - Purba, Bernadetha Eveline Gabriella; Nuzula, Nila Firdausi; Sugiastuti, Reika Happy (Profit: Jurnal Adminsitrasi Bisnis, 2023)
This research used Working Capital to Total Asset (WCTA), Debt to Equity Ratio (DER), and Inventory Turnover Ratio (IT) as independent variables. This research’s goals are to know and to explain the influence of WCTA on Profit Growth, the influence of DER on Profit Growth, the influence of IT on Profit Growth and the influence of WCTA, DER, and IT simultaneously on Profit Growth. The background of this research is the importance of companies to enhance profit from time to time as a form of responsibility to the Investor. This study is an explanatory research with quantitative approach. The object of this research is food and beverage companies that listed in Indonesia Stock Exchange (IDX) period 2017-2020. The sample selection is a purposive sampling and as a result, 16 companies were chosen from total population of 30 companies. The results of this research show that the influence of WCTA, DER, and IT simultaneously were significant on Profit Growth, and the influence IT also showed a significant impact on Profit Growth even though in the different direction. On the otherhands, WCTA and DER partially had an insignificantly influence on Profit Growth.